Acute psychosocial care of families in paediatric resuscitation settings: Variables associated with parent emotional response. (September 2021) - Manguy, Alys-Marie; Oakley, Ed; Gordon, Rob; Joubert, Lynette
Abstract: Background: Family presence in paediatric resuscitation settings is now accepted practice. However, there is limited evidence to guide psychosocial care of these families. This study aimed to increase the understanding of family demographics and needs for psychosocial care at the Royal Children's Hospital, Melbourne, Australia and to identify the factors that impact on families at this time of emotional and social distress. Method: A retrospective clinical data-mining methodology was utilised (n = 1123). Descriptive and inferential data analysis was undertaken using STATA software to identify population demographics, patterns in service usage and family experience, and to identify factors associated with parents' emotional responses. Findings: Four areas were identified that support evidence-informed psychosocial care for families in paediatric resuscitation contexts: 1) family and parent dynamics 2) families' experiences of distress in relation to patient diagnostic category 3) systemic nature of family response, and 4) the identification and analysis of family emotional support needs, which is central to the psychosocial response.